Analisis Laporan Arus Kas Dalam Menilai Kinerja Keuangan Pada PT. Unilever Indonesia, Tbk - Sri Rosmawati; Rizki Hayatun Hasibuan (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT STIE-GRAHA KARYA MUARA BULIAN, 2020)
The purpose of this study is to assess the financial performance of PT. Unilever Indonesia, Tbk seenfrom the statement of cash flows using the ratio of operating cash flows, the ratio of capitalexpenditures, the ratio of total debt, and the ratio of cash flows to net income in 2014 to 2018.Theanalytical method used is descriptive qualitative and quantitative. And use data analysis tools in theform of cash flow ratios, such as operating cash flow ratios, capital expenditure ratios, ratio of totaldebt and ratio of cash flows to net income.As for the results of the analysis of cash flow ratios, such asOperating Cash Flow Ratios from 2014-2018 of 0.73, 0.62, 0.62, 0.56 and 0.71 show poor financialperformance. The Capital Expenditure Ratio from 2014-2018 of 5.74, 4.28, 3.74, 4.39 and 7.93 showsgood financial performance. The ratio of Total Debt from 2014-2018 of 0.67, 0.58, 0.56, 0.51 and 0.66shows the financial performance is not good. The ratio of Cash Flow to Net Income from 2014-2018 of1.13, 1.08, 1.05, 1.01 and 0.87 shows good financial performance. So the results of the ratio that hasbeen analyzed can be concluded that the financial performance seen from the cash flow statement of PT. Unilever Indonesia, Tbk from 2014 to 2018 showed a good ratio of analysis results.